(untitled) (Web of Teachers: Inderscience Research, 2026)
This section examines the importance of understanding the relationship between pictorial words and holistic pictorial expressions in the translation process. Figurative language, including metaphors, idioms, and expressive phrases, often carries meanings that are different from their literal interpretation. It is imperative for students in the translation process to recognize that individual figurative words can contribute to a more comprehensive pictorial expression, the meaning of which can only be understood in context. The study emphasizes the need for contextual analysis, semantic awareness, and cultural understanding when translating figurative expressions. By using appropriate translation strategies, students can accurately convey the intended meaning of pictorial language while preserving stylistic and communicative effects. Developing this skill helps learners avoid literal translation errors and improve the overall quality and impact of translated texts.